PARTISIPASI MASYARAKAT DALAM PROGRAM RELOKASI PERMUKIMAN PENDUDUK TAHUN 2012-2014 (Studi Kasus Relokasi Permukiman Bantaran Sungai Bengawan Solo di Kelurahan Sangkrah dan Kelurahan Joyosuran Kota Surakarta) - sugesti, Risna; Harsasto, Priyatno; ., Turtiantoro (Journal of Politic and Government Studies, 2015)
This research is aimed at finding out the general description of resettlement program in Bengawan Solo riverbank area in Surakarta Municipality. Thegeneral description includes program background and purpose, resettlement process (from census to accountability presentation), and the resettlement committee membership. Another aim is to figure out the formation of work groups in Sangkrah and Joyosuran village and the performance of those work groups along with the government in dealing with the people who refuses to be relocated. Based on the method of data analysis, this research is qualitative and belongs to the descriptive-analytical category which aims to provide systematic, accurate, and factual on research data and its interrelation with the phenomenon being studied.Results show that people are participating in the resettlement process from the beginning (census) through the accountability presentation. The process of work group formation in Sangkrah and Joyosuran village in Surakarta Municipality is a model of deliberate participation that involves all related political entities (village chief and his/her staff, LPMK, community leaders, and the affected community). They sat together in a forum of dialog (RembugWarga) that facilitates ideas exchange, discussion, and consultation with and among the parties present. The hindrances that affect resettlement program are some part of the community that still refuses the program, the different abilities of each work group, and the limited budget set by the regional government. The attempts made by the work group along with the municipal government of Surakarta focus on persuasive approaches that put people empowerment first. These attempts were made easier by the trust of the community to the resettlement program. The result is 64% resettlement realization in Sangkrah village, and 91% resettlement realization in Joyosuran village during 2012 through 2014.Keywords: people’s partiipation, relocation, Sangkrah, Joyosuran, Surakarta